Understanding the effect of milk composition and milking season on quality characteristics of chhana. Issue 1 (11th October 2020) - Chakraborty, Purba; Singh, Tejvir; Shivhare, Uma Shanker; Basu, Santanu
Abstract: The quality characteristics of chhana varied due to the milk composition (cow‐, buffalo‐, and mixed‐ milk) which in turn was affected by the milking season (summer and winter). Upon heating and acidification of milk samples water holding phenomena and denatured protein association within and with other components lead to variation in both macroscale properties (color, texture, and rheology) and molecular bonding patterns (FTIR character). Yield, lightness ( L * value), textural firmness, and elastic modulus of chhana increased with increasing proportion of buffalo milk in mixed milk due to higher total solids and less moisture content in both the seasons. Total protein, fat, water, and interaction between them and extent of hydrogen bonding significantly affected the rheological and textural properties of chhana samples. Abstract : Effect of milk composition and milking season on chhana (Indian cottage cheese). BM, buffalo milk; CM‐cow milk; CP, casein protein; MF, milk fat; MM, mixed milk; tanδ, phase angle;, W, water; WP, whey protein., cow milk chhana properties (firmness and stickiness);, , buffalo milk chhana properties (firmness and stickiness) indicative of specific components in FTIR region; blue—CM; red—BM.